The possible role of HCN in the biology and feeding behavior of the cassava burrowing bug (Cyrtomenus bergi Froeschner: Cydnidae: Hemiptera) - Bellotti, T.; Arias, V.B. (International Center for Tropical Agriculture, 1993)
The burrowing bug, C. bergi (Hymenopetra: Cydnidae) was first recorded as a cassava pest in Valle, Colombia, in 1979. Nymphs and adults of this subterranean sucking insect feed on cassava roots by means of a thin, strong stylet. As it feeds, it inoculates the roots with soil-borne pathogens such as Diplodia, Fusarium, Phytopthora and Phythium spp. Brown or black lesions develop on the white, fleshy root, rendering it commercially unacceptable. Cassava root darnage can reach 70 to 80 of total roots with more than 50 reduction in starch content. Additional hosts include onion, peanuts, maize, sorghum, sugar-cane, coffee, pasture grasses, potatoes and numerous weed species. Studies show that C. bergi develops faster on maize than on cassava, and prefers maize over cassava in free choice test (78 vs 22). Field trials suggest resistance to C. bergi may be related to HCN content of the roots. In laboratory tests adults and nymphs fed on a high HCN clone had larger nymphal development, reduced adult longevity, reduced egg production and increased mortality. On CMC 40 (low HCN) nymphal mortality was 56, while on high HCN clone MCol 1684, mortality reached 84. On CMC 40, 50 mortality occurred at 35 days (r2=0.96); for MCol 1684, at 28 days (r2= 0.98). Highest mortality occurred during the first two instars when nymphs primarily feed on the root peel. These results constitute one of the few documented cases where HCN content in cassava may be related to arthropod resistance.